Financial Stability and Firms’ Performance: A Study of Selected Oil and Gas Firms in Nigeria: Array - Osamor, Ifeoma Patricia; Adebanjo, Adebola Muyideen (Acta Universitatis Danubius. Œconomica, 2020)
The relationship between financial stability and performance measurement has been an issue of discussion in recent past. Considering the over-dependence of Nigerian economy on Oil and Gas, the study therefore investigates financial stability of Oil and Gas firms’ in relation to their performance. Secondary data which were sourced from Annual reports of seven (7) Oil and Gas firms for twelve years (2007 – 2018) were used for the study. The model estimation showed that Return on Assets (ROA) serves as proxy for performance indicator while Fixed Asset Ratio, Proprietary Ratio, Debt Ratio and Equity Ratio serve as proxy for financial stability indicators. The study made used of descriptive statistics and panel data regression estimation technique to analyze the data. The results of the study showed that financial stability ratios have no effects on firms’ performance, while financial risk ratios have effects on firm’s performance in Oil and Gas firms. The study concluded that financial stability ratios (fixed assets ratio and proprietary ratio) do not influence firms’ performance, while, financial risk ratios (debt and equity ratio) do influence firms’ performance. Thus, the recommendation to Oil & Gas sectors managers is to develop a sustainable yardstick to curtain the use of debt source of finance in order to implement capital projects that yield no immediate returns.